Perilaku Pencegahan COVID-19 pada Pekerja Manufaktur di PT X - Saputri, Budiarti Agung; Indarjo, Sofwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: PT X is a manufacturing company that employs more than 5,000 workers in factory. There were 688 new cases of COVID-19 during the 2 months following the joint leave. As many as 85% of manufacturing workers choose to use cheap, comfortable, and stylish masks. This is supported by the behavior of workers who neglect to wear masks and keep their distance when in crowds. The purpose of this study was to determine the factors that influence the behavior of preventing COVID-19 in manufacturing workers at PT X. Methods: This type of research is analytic observational using a cross sectional design. Simple random sampling technique with 406 sample of respondents. The research instrument used a questionnaire through an online form and was analyzed using the Chi Square test (α = 0.05). Results: There is a relationship between COVID-19 prevention behavior with attitude (0.001), use of company health facilities (0.001), and coworker support (0.001). There isn’t relationship between COVID-19 prevention behavior with age (0.108), gender (0.726), and level of knowledge (1.000). Conclusion: There’s a significant relationship between attitude, use of company health facilities, and coworker support with COVID-19 prevention behavior. Attitude, company facilities, and supportive colleagues are factors that influence the behavior of preventing COVID-19 among workers.